Multicenter Retrospective Study of Neurostimulation With Exit of Therapy by Explant. Issue 6 (17th July 2017) - Pope, Jason E.; Deer, Timothy R.; Falowski, Steven; Provenzano, David; Hanes, Michael; Hayek, Salim M.; Amrani, Jacob; Carlson, Jonathan; Skaribas, Ioannis; Parchuri, Kris; McRoberts, W. Porter; Bolash, Robert; et al.
Abstract : Introduction: Spinal cord stimulation (SCS) devices are cost effective and improve function as well as quality of life. Despite the demonstrated benefits of SCS, some patients have the device explanted. We are interested in exploring the patient characteristics of those explanted. Methods: This is a retrospective chart review of neurostimulation patients who underwent explantation at 18 centers across the United States within the previous five years. Results: Data from 352 patients were collected and compiled. Failed Back Surgery syndrome was the most common diagnosis (38.9%; n  = 136/350) and over half of the patients reported numerical rating scale (NRS) scores ≥8 prior to implant (64.3%; n  = 207/322). All patients reported changes in NRS scores across time, with an initial decrease after implant followed by a pre‐explant increase ( F (2, 961) = 121.7, p  < 0.001). The most common reason for device explant was lack or loss of efficacy (43.9%; 152/346) followed by complications (20.2%; 70/346). Eighteen percent (18%; 62/343) of patients were explanted by a different physician than the implanting one. Rechargeable devices were explanted at a median of 15 months, whereas primary cell device explants occurred at a median of 36 months (CI 01.434, 2.373; median endpoint time ratio = 2.40). Discussion: Loss or lack of efficacy and complications with therapy represent the most frequent reasons for neurostimulation explantation. Of the devices that were explanted, therapy was terminated earlier when devices were rechargeable, when complications occurred, or when pain relief was not achieved or maintained. Furthermore, in nearly 20% of the cases, a different provider than the implanting physician performed device removal. Conclusions: SCS is largely a safe and efficacious strategy for treating select chronic refractory pain syndromes. Further prospective data and innovation are needed to improve patient selection, maintain SCS therapeutic efficacy and reduce the reasons that lead to device explant.